Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/la0520841
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Hierarchical Meso- and Macropore Architectures by Liquid Crystalline and Polymer Colloid Templating

Abstract: The generation of porous silica with hierarchically organized bimodal mesoporosity of adjustable size and well-defined shape was investigated by using surfactant mixtures and the nanocasting procedure (liquid crystalline templating). A systematic study of combinations of various block copolymers (Pluronics F127, KLE (poly(omega-hydroxypoly(ethylene-co-butylene)-co-poly(ethylene oxide))) and SE (PS-co-PEO)) with smaller surfactants (Pluronics P123, C16mimCl, and CTAB) revealed that hierarchical bimodal mesopore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 50 publications
3
133
0
3
Order By: Relevance
“…18 -20 However, multiple use of surfactants have been known to have some problems of complex interactions among templates. 20 Therefore, the use of building blocks, having nanopores within the structures, as the pore wall components can circumvent such a problem.…”
Section: -8mentioning
confidence: 99%
“…18 -20 However, multiple use of surfactants have been known to have some problems of complex interactions among templates. 20 Therefore, the use of building blocks, having nanopores within the structures, as the pore wall components can circumvent such a problem.…”
Section: -8mentioning
confidence: 99%
“…Indeed, it was reported that a hierarchical combination of mesopores reduces transport limitations in catalysis, resulting in higher activities and better controlled selectivity [27] . Therefore, over the past few years the development of these hierarchically ordered structures at multiple length scales has attracted much attention and materials with a micro-macroporous or a meso-macroporous structure have been synthesized using multiple templates through either soft or hard templating methods [28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchy in size and pore interconnection have been judged to be equally, if not more, important in terms of final application because of the much easier control that one can establish on the diffusion properties inside the pores. 4,5,6 Typically, organic templates are currently used to obtain micro-or meso-scale porosity such as in zeolites (use of quaternary ammonium salts) or in MCM-41 or SBA-15 materials (use of surfactant micelles). 7,8 Ordered macroporosity is easily achieved using micrometer-sized colloidal packing.…”
Section: Introductionmentioning
confidence: 99%